2008
DOI: 10.1039/b718770j
|View full text |Cite
|
Sign up to set email alerts
|

Activation of two C–H bonds of NHC N-methyl groups on triosmium and triruthenium carbonyl clusters

Abstract: The thermolysis of the NHC triosmium cluster [Os3(Me2Im)(CO)11] (1a; Me2Im = 1,3-dimethylimidazol-2-ylidene) in toluene at reflux temperature sequentially affords the edge-bridged cluster [Os3(micro-H)(micro-kappa2-MeImCH2)(CO)10] () and the face-capped derivative [Os3(micro-H)2(micro3-kappa2-MeImCH)(CO)9] (3a). These products result from the sequential oxidative addition of one (2a) and two (3a) N-methyl C-H bonds of the original NHC ligand. The related face-capped triruthenium cluster [Ru3(micro-H)2(micro3-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…23 The strong basicity of the NHC ligands of 11-13 promotes the easy oxidation of these electron-rich ruthenium(0) complexes. 24 Therefore, these products result from the sequential oxidative addition of one (17) and two (18) N-methyl C-H bonds of the original Me 2 Im ligand (Scheme 6). Similar C-H bond activation processes have been observed upon heating the acyclic aminocarbene cluster [Os 3 {C(Et)NMe 2 }(CO) 11 ].…”
Section: Ruthenium and Osmium Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The strong basicity of the NHC ligands of 11-13 promotes the easy oxidation of these electron-rich ruthenium(0) complexes. 24 Therefore, these products result from the sequential oxidative addition of one (17) and two (18) N-methyl C-H bonds of the original Me 2 Im ligand (Scheme 6). Similar C-H bond activation processes have been observed upon heating the acyclic aminocarbene cluster [Os 3 {C(Et)NMe 2 }(CO) 11 ].…”
Section: Ruthenium and Osmium Clustersmentioning
confidence: 99%
“…25 The related face-capped triruthenium cluster [Ru 3 (m-H) 2 (m 3 -k 2 -MeImCH)(CO) 9 ] (19) has been prepared by heating [Ru 3 (Me 2 Im)(CO) 11 ] (1) in THF at reflux temperature. 24 In this 24 The bonding in the ruthenium cluster 19 has been studied from the perspective of the atoms in molecules (AIM) quantum theory (Fig. 2).…”
Section: Ruthenium and Osmium Clustersmentioning
confidence: 99%
“…2 However, since the first study of the reaction of Ru 3 (CO) 12 with tetraaminealkenes (IEt 2 H 2 ) 2 to give complex Ru 3 (CO) 11 (IEt 2 H 2 ) reported by Lappert and Pye in 1977, 3 only a few reports dealing with Ru 3 (CO) 12 and NHCs ligands have been published. [4][5][6][7][8][9][10][11] Among these reactions, some abnormal intramolecular C-X (X = H, N) bond cleavage was observed. Cabeza et al demonstrated the synthesis of [Ru 3 (CO) 11 (Me 2 Im)] (Me 2 Im=1,3dimethylimidazol-2-ylidene) and its transformation into [Ru 3 (m-H) 2 (MeImCH)(CO) 9 ] through a process involving unusual reversible cleavage of two C-H bonds of a N-methyl group.…”
Section: Introductionmentioning
confidence: 99%
“…However, hydride bridging typically increases the Ru−Ru bond distances ranging from 2.9 to 3 Å or slightly more [57–61] . Interestingly, this behavior was also observed in oxazole derived NHC Ru complexes wherein one of the two hydride bridged Ru−Ru bond distances was the highest i. e., 3.133 Å [58] . The Ru−Ru bond distances are conveniently illustrated from the molecular structure or the single crystal XRD studies of the clusters.…”
Section: Metal‐metal Interactions In Ru Nhc Complexesmentioning
confidence: 84%
“…When carefully studied, they reveal that the ruthenium clusters of normal or abnormal NHCs have a Ru−Ru bond distance ranging from 2.7 to 2.9 Å. However, hydride bridging typically increases the Ru−Ru bond distances ranging from 2.9 to 3 Å or slightly more [57–61] . Interestingly, this behavior was also observed in oxazole derived NHC Ru complexes wherein one of the two hydride bridged Ru−Ru bond distances was the highest i. e., 3.133 Å [58] .…”
Section: Metal‐metal Interactions In Ru Nhc Complexesmentioning
confidence: 92%